1984
DOI: 10.3133/ofr84886
|View full text |Cite
|
Sign up to set email alerts
|

Geologic map of southeastern Alaska

Abstract: Open-Fi le Report 84-886This report is preliminary and has not been reviewed for conformity with U.S. Geological Survey editorial standards and stratigraphic nomenclature.*~n c h o r a~e ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 30 publications
2
47
0
Order By: Relevance
“…The main plutons in the Coast Mountains can be divided into several suites of differing age, composition, and intrusive style (Buddington and Chapin, 1929;Barker et al, 1986;Brew, 1988;Gehrels et al, 1991b;Gehrels and Berg, 1992) (Fig. 2).…”
Section: Plutonic Suitesmentioning
confidence: 99%
See 3 more Smart Citations
“…The main plutons in the Coast Mountains can be divided into several suites of differing age, composition, and intrusive style (Buddington and Chapin, 1929;Barker et al, 1986;Brew, 1988;Gehrels et al, 1991b;Gehrels and Berg, 1992) (Fig. 2).…”
Section: Plutonic Suitesmentioning
confidence: 99%
“…This body was originally reported to intrude strata of the Gravina belt (Berners Formation of Knopf, 1911), but Redman (1984) reported that the contact is at least locally nonconformable. This conclusion has been controversial because strata of the Gravina belt are Upper Jurassic-Lower Cretaceous (Berg et al, 1972), and most plutons along the west flank of the Coast Mountains are mid-Cretaceous in age (Brew and Morrell, 1983;Gehrels and Berg, 1992).…”
Section: Cretaceous Plutonsmentioning
confidence: 99%
See 2 more Smart Citations
“…), in addition to other, more radiogenic rocks in the fluid-reaction path that would account for the variation in Pb ratios. Such a close link to older source rocks is particularly evident for the Niblack deposit, which notably is hosted by felsic metavolcanic and tuffaceous metasedimentary rocks that resemble the lithologic sequence in the Wales Group (Gehrels and Berg, 1992;Maas and others, 1995). Detrital zircons dated by U-Pb Pb ratios for Ordovician mantle from primitive intraoceanic arcs in Newfoundland (Swinden and Thorpe, 1984;Swinden, 1996) and for Devonian mantle from a primitive island arc associated with massive sulfide deposits in the Klamath Mountains, Calif. (Shasta; Doe and others, 1985).…”
Section: Lead Sources: Massive Sulfide Deposits In the Moira Sound Unitmentioning
confidence: 99%